Psikoedukasi Membangun Motivasi Bersama Psikologi Upaya Meningkatkan Kualitas di Komunitas Gemar Belajar dan Komunitas Senyum Anak Nusantara Banjarmasin - Anjar Sri Lestari; Sulastri, Indah; Rizqi Amalia Arpianty; Gt. M. Rizqi Yusril Natsir Mahendra; Jessica Putri Lestari; Najwa Nur Fatimah; Wardatun Nisa (Borneo Community Development, 2025)
This study aims to examine the effectiveness of psychoeducation in enhancing the motivation of community members. The subjects of the study were members of the Gemar Belajar (GemBel) Community and the Senyum Anak Nusantara (SAN) Community in Banjarmasin who experienced a decline in motivation. The methods used included material presentation, ice-breaking activities, and Focus Group Discussion (FGD). The results showed that participants experienced an increase in motivation after attending the psychoeducation activities, as evidenced by significant differences between pretest and posttest responses. The psychoeducation provided included material on ways to boost motivation, such as identifying the root causes of problems, making small changes, and recalling goals. In conclusion, psychoeducation is effective in enhancing the motivation of community members, which is crucial for the success and sustainability of the community.